"The Banks are Our Stages": Flo6x8 and Flamenco Performance as Protest in Southern Spain. Issue 2 (15th March 2019) - Brown, Joshua
Abstract: In May 2011, a widespread protest movement known as 15M emerged in Spain, emphasizing the sustained and purposeful occupation of public spaces. Based in Seville, the performance collective Flo6x8 protests financial and political malfeasance in Spain by converting corporate banks into flamenco performance and recording spaces. This article explores how Flo6x8 generates new physical and conceptual spaces for political expression and protest in Spain's 15M Movement through their pioneering use of digital media, flash mobs, and flamenco performance. Flo6x8 temporarily converts spaces of the opposition into oppositional spaces and channels public outrage into powerful and irreverent productions. The group appropriates enduring symbols and associations of flamenco, including poverty and alienation, while simultaneously challenging notions of where and when performances of flamenco should happen. Drawing from literature in performance studies, theory of social movements, critical urban theory, and ethnographies of precarity and austerity in southern Europe, this article considers how visual, corporeal, and spatial elements are critical factors that shape the meanings of flamenco performance and protest in twenty-first-century Spain.